Peranan Kontrol Struktural dan Hidrologis dalam Perkembangan Lorong Gua Bagus-Jebrot di Malang-Indonesia - Mohammad Ainul Labib; Agung Suprianto; Devi Prasetyo; Aan Seftian Hardianto; Alfi Sahrina; Syaiful Effendi; Joko Agus Triyono; Febria Ika Rustyana; Ayu Romadhoni (Universitas Lambung Mangkurat, 2020)
Bagus-Jebrot Cave is located in Donomulyo District, Malang Regency which is in the Wonosari Formation which was formed in the Middle Miocene and Late Miocene. The purpose of this study is related to the developmental control that affects the cave passageways. The approach used is a geomorphological approach by conducting field measurements and documentation. The analysis used is frequency analysis and cross-section of the passage. Bagus-Jebrot Cave is a type of Epigenic Cave which is formed from surface water flowing into doline/sinkhole. It can be seen from the planview map that has a curvilinear passage pattern. The existence of groundwater flow also forms a physiographic cave passage with ellipse passage formation, asymmetrical ellipse, potholes, callops, solution notches, cups, solution pockets. Besides underground water flow, the development of the Bagus-Jebrot Cave aisle is related to the process of structural lifting and control. The lifting process is marked by the formation of 4 levels of the cave passage. While the formation of the canyon, joint passage, rectangular passage and keyhole is the result of structural control